PERANCANGAN BUKU FOTOGRAFI EMPON-EMPON DENGAN TEKNIK ENVIRONMENTAL PORTRAIT SEBAGAI SARANA PENGENALAN KEPADA REMAJA - Hari Saputera, Rizal Amandara; Budiardjo, Hardman; Dewanto, Thomas Hanandry (Jurnal Art Nouveau, 2017)
Abstract: Medicinal currently almost alienated and less attractive to teens because of the large reduction of land occurred and the emergence of a wide range of modern processed food. This happens due to lack of awareness to appreciate and preserve the original heritage of Indonesia. Medicinal include one legacy that must be preserved, therefore the purpose of this study was to design a photography book medicinal portrait with environmental engineering as a means of introduction to adolescents. Medicinal is part of the culture in Indonesia where the plant is located. In the midst of the massive land reduction and fast food that presents a wide range of selection, medicinal began to be forgotten among teenagers. From the analysis of these data, obtained keyword